2011
DOI: 10.1101/lm.024554.111
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus is required for paired associate memory with neither delay nor trial uniqueness

Abstract: Cued retrieval of memory is typically examined with delay when testing hippocampal functions, as in delayed matching-tosample tasks. Equally emphasized in the literature, on the other hand, is the hippocampal involvement in making arbitrary associations. Paired associate memory tasks are widely used for examining this function. However, the two variables (i.e., delay and paired association) were often mixed in paired associate tasks, and this makes it difficult to localize the cognitive source of deficits with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 64 publications
3
24
1
Order By: Relevance
“…Although one may predict that this task may have been solved easily by associating egocentric responses with cueing objects (which is not known to be hippocampal dependent), surprisingly, inactivation of the dorsal hippocampus with muscimol severely disrupted normal performance for two consecutive days. We confirmed that the rats used visual cues in the background by showing that rats were not able to do this task in the dark either with or without hippocampal inactivations (Yoon et al, 2012). We also showed that rats were able to perceptually discriminate the cueing objects in the dark (presumably using tactile information).…”
Section: Categories Of Contextual Behavior and Brain Regionssupporting
confidence: 77%
See 1 more Smart Citation
“…Although one may predict that this task may have been solved easily by associating egocentric responses with cueing objects (which is not known to be hippocampal dependent), surprisingly, inactivation of the dorsal hippocampus with muscimol severely disrupted normal performance for two consecutive days. We confirmed that the rats used visual cues in the background by showing that rats were not able to do this task in the dark either with or without hippocampal inactivations (Yoon et al, 2012). We also showed that rats were able to perceptually discriminate the cueing objects in the dark (presumably using tactile information).…”
Section: Categories Of Contextual Behavior and Brain Regionssupporting
confidence: 77%
“…We tested recently whether those additional cognitive processes mentioned above were critical in testing hippocampal functions for contextual item–response selection by using a simpler paradigm (Yoon et al, 2012). In our task, the rat just ran along a straight track (thus with almost no requirement for spatial navigation) upon exiting a start box and encountered a toy object at the end of the track (Figure 8).…”
Section: Categories Of Contextual Behavior and Brain Regionsmentioning
confidence: 99%
“…Interestingly, patients and controls performed similarly on the orientation discrimination task, suggesting a relative specificity of findings for memory processes, that is, the deficit cannot be explained by reduced sensory capacities leading to a failure to differentiate the orientation of the stimuli. Consistent with this finding, Yoon, Seo, Kim, and Lee (2011) demonstrated that pharmacological inactivation of the dorsal hippocampus in animal experiments disrupted paired associates learning, whereas it did not affect the discrimination of individual objects or locations.…”
Section: Discussionsupporting
confidence: 65%
“…More specifically, we show that pharmacologically enhancing sleep spindles in healthy adults produces exceptional memory performance beyond that seen with sleep alone (placebo) or sleep with the comparison drug (SO). The hippocampus has previously been shown to particularly engage learning of associative elements (Davachi and Wagner, 2002; Yoon et al, 2012), and associative verbal learning has been correlated with sleep spindles (Gais et al, 2002; Schabus et al, 2004; Clemens et al, 2005; Schmidt et al, 2006). We, therefore, used an associative verbal learning task to test the prediction that sleep spindles play a critical role in hippocampal-dependent memory consolidation.…”
Section: Discussionmentioning
confidence: 99%